The regulatory role of peripheral blood mononuclear cell function by A20 - Xuan, Nguyen Thi; Hoang, Nguyen Huy (Vietnam Journal of Biotechnology, 2020)
Peripheral blood mononuclear cells (PBMC) consist of lymphocytes (T cells, B cells, natural killer cells), monocytes and dendritic cells and play important roles in initiating and regulating immunity against pathogens or immunotolerance to allergens. Activation of PBMCs is induced upon exposure to multiple stimuli by the binding with toll-like receptors (TLRs), recognition elements of the innate immune system. A20 is a negative regulator of nuclear factor (NF)-κB-dependent immune reaction in response to TLR ligands. A20-deficient mice display severe inflammation, tissue damage in multiple organs, cachexia and premature mortality. Single nucleotide polymorphisms (SNPs) at A20 gene region in humans reduce the binding capacity of A20 to NF‐κB subunits, resulting in reduced expression and function of A20 and leading to the pathogenesis of autoimmune and cancers. Although the inhibitory role of A20 on immune cells including B, T and DC functions has been previously reported, the effect of A20 on PBMC function is not mentioned yet. The present study, therefore, explored whether A20 expression is involved in immunophenotypic changes, the release of cytokine production, cell migration, and apoptosis. To this end, immonophenotypic profile and cell apoptosis were examined by flow cytometry, secretion of inflammatory cytokines by ELISA and cell migration by a transwell migration assay. As a result, percentages of CD3+CD25+, CD19+CD25+, and CD11b+CD40+ expressing cells, the release of TNF-α and IL-1β and cell migration were enhanced in A20-silenced PBMCs. However, cell apoptosis was independent of the presence of A20 in PBMCs. In conclusion, these results attained in this study suggested that A20 expression might modulate the immune response in autoimmune disease and cancers.